Reification and assent in research involving those who lack capacity - Smajdor, Anna (Journal of medical ethics, 2023)
In applied ethics, and in medical treatment and research, the question of how we should treat others is a central problem. In this paper, I address the ethical role of assent in research involving human beings who lack capacity. I start by thinking about why consent is ethically important, and consider what happens when consent is not possible. Drawing on the work of the German philosopher Honneth, I discuss the concept of reification—a phenomenon that manifests itself when we fail to observe or respond to our fellow humans’ need for recognition. I suggest that assent is a way of responding to this moral need for recognition, which exists independently of cognitive capacity. I will look at the circumstances in which consent cannot be obtained from human beings, and ask whether some of the same ethically important considerations that underpin the need for consent might be achieved through seeking assent. I discuss the ways in which this might be beneficial for researchers, for prospective research participants and for society at large.